STUDY OF THERMOMECHANICAL EFFECTS OF MAIN CHAIN LIQUID CRYSTAL ELASTOMER AS FUNCTION OF CROSSLINKER CONCENTRATION - Irna Farikhah; Yusril Yusuf (Jurnal Sains Materi Indonesia, 2011)
STUDY OF THERMOMECHANICAL EFFECTS OF MAIN CHAIN LIQUID CRYSTAL ELASTOMER AS FUNCTION OF CROSSLINKER CONCENTRATION. Thermomechanical effects of dry Main Chain Liquid Crystal Elastomer (MCLCE) with the different concentration of crosslinker 8 %, 12 %, 14% and 16% have been studied. Length of MCLCE monotonically shrinks parallel to the director, while it expands perpendicularly to the director, with a somewhat faster change at nematic isotropic transition phase, Tni. The result of the investigation showed that the value of maximum contraction is greater and faster than maximum expansion.